Method for producing curable composition

JP2025029914APending Publication Date: 2025-03-07KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023134803
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0007】 本発明の一態様によれば、伸びおよび強度を両立した硬化物を与える硬化性組成物の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029914000001
    Figure 2025029914000001
Patent Text Reader

Abstract

To provide a method for producing a curable composition that yields a cured product with both of elongation and strength.SOLUTION: A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) and (2): (1) a step of mixing (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) a compound having an amino group; and (2) a step of adding (C) a curing catalyst to the mixture prepared in the step (1). (A) The (meth)acrylic polymer having the alkoxysilyl group is a polymer that satisfies specific conditions.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a curable composition. [Background technology]

[0002] Polymer molecules having alkoxysilyl groups form siloxane bonds with other polymer molecules as a result of hydrolysis of the alkoxysilyl groups. This crosslinking reaction produces a rubber-like cured product. Curable compositions containing such polymer molecules are used in sealing materials, adhesives, paints, etc. (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2023 / 048155 Brochure Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional curable compositions have room for improvement in terms of achieving both elongation and strength in the resulting cured product.

[0005] An object of one aspect of the present invention is to provide a method for producing a curable composition that gives a cured product that has both elongation and strength. [Means for solving the problem]

[0006] A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) and (2): Step (1): (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) a compound having an amino group are mixed together; Step (2): adding a curing catalyst (C) to the mixture obtained in step (1); The (A) (meth)acrylic copolymer having an alkoxysilyl group has a molecular weight distribution (Mw / Mn) of 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, the number of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, The repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block. Effect of the Invention

[0007] According to one aspect of the present invention, there is provided a method for producing a curable composition that gives a cured product that has both elongation and strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] 1. Method for Producing Curable Composition and Cured Product A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) and (2). Step (1): A step of mixing (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) a compound having an amino group. Step (2): A step of adding a curing catalyst (C) to the mixture obtained in the above step (1).

[0009] In step (1), (D) phosphoric acid ester may be further mixed. In this case, the order of mixing (A) (meth)acrylic copolymer having an alkoxysilyl group, (B) compound having an amino group, and (D) phosphoric acid ester in step (1) is not particularly limited. Each component may be mixed in any order, or all components may be mixed at once. Preferably, (A) (meth)acrylic copolymer having an alkoxysilyl group and (B) compound having an amino group are mixed, and then (D) phosphoric acid ester is added and further mixed.

[0010] In step (1), (E) a polyoxyalkylene polymer having a silyl group may be further mixed. In this case, the order of mixing (A) the (meth)acrylic copolymer having an alkoxysilyl group, (B) the compound having an amino group, and (E) the polyoxyalkylene polymer having a silyl group in step (1) is not particularly limited. Each component may be mixed in any order, or all components may be mixed at once. Preferably, (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group are mixed first, and then (B) the compound having an amino group (and (D) the phosphoric acid ester, which is an optional component) is added and mixed.

[0011] In the conventional curable compositions, for example, (A) a (meth)acrylic copolymer having an alkoxysilyl group, (B) a compound having an amino group, and (C) a curing catalyst were mixed simultaneously, or a mixture of (B) a compound having an amino group and (C) a curing catalyst was added to (A) a (meth)acrylic copolymer having an alkoxysilyl group and mixed. In this case, the curing of the curable composition started at the time of mixing these three components.

[0012] However, the present inventors have found that by first mixing (A) an alkoxysilyl group-containing (meth)acrylic copolymer and (B) an amino group-containing compound, and then adding and mixing (C) a curing catalyst, the curable composition can be stored without curing (so that it is now possible to prepare a one-liquid curable composition, which was previously impossible). Furthermore, it has been found that the cured product obtained from this curable composition has both elongation and strength.

[0013] According to the production method of one embodiment of the present invention, both one-component curable compositions and multi-component curable compositions can be produced. A one-component curable composition can be obtained by mixing (A) an alkoxysilyl group-containing (meth)acrylic copolymer and (B) an amino group-containing compound, and then adding (C) a curing catalyst to the composition, and storing the composition in a container for storage. A multi-component curable composition can be obtained by mixing (A) an alkoxysilyl group-containing (meth)acrylic copolymer and (B) an amino group-containing compound, and storing the mixture in a first container, and storing (C) a curing catalyst in a second container, and storing the mixture in a container for storage.

[0014] A cured product is obtained by curing the curable composition obtained by the above-mentioned manufacturing method. For example, the curable composition can absorb ambient moisture and spontaneously change into a cured product by the above-mentioned manufacturing method. The use of the cured product is not particularly limited. Examples include architectural and industrial sealants, electrical and electronic component materials (such as solar cell back sealants), electrical insulating materials (such as insulating coating materials for wires and cables), pressure sensitive adhesives, adhesives, elastic adhesives, contact adhesives, tile adhesives, paints, coating materials, sealing materials for can lids, etc., potting agents for electrical and electronic use, films, gaskets, casting materials, various molding materials, artificial marble, rust-proofing and waterproofing sealants for cut parts of wire-reinforced glass or laminated glass, and waterproofing agents.

[0015] In one embodiment, the cured product is in the form of a film. Therefore, the present invention also includes a method for producing a film, which comprises a step of curing the curable composition obtained by the above-mentioned production method. The lower limit of the thickness of the produced film can be 0.1 mm or more, 0.5 mm or more, 1 mm or more, 5 mm or more, or 10 mm or more. The upper limit of the thickness of the produced film can be 100 mm or less, 90 mm or less, 80 mm or less, 70 mm or less, 60 mm or less, or 50 mm or less.

[0016] The film-like cured product can be produced, for example, by applying the curable composition to a substrate and then curing it. The film may be used in a state where it is peeled off from the substrate, or in a state where the substrate and the film are integrated. Examples of applications of the film-like cured product include sealing materials, coating agents, and adhesives.

[0017] 2. Components contained in the curable composition The components contained in the curable composition, including optional components, will be described below.

[0018] [2.1. (A) (Meth)acrylic copolymer] [2.1.1. Structure of (meth)acrylic copolymer] The (meth)acrylic copolymer has an X block and a Y block, and contains an XY diblock structure or an XYX triblock structure in the molecule. The structure of the entire molecule of the (meth)acrylic copolymer is not particularly limited as long as it contains an XY diblock structure or an XYX triblock structure, and may be, for example, an XYXY tetrablock structure.

[0019] Here, the term "XYX triblock structure" refers to what is generally known by those skilled in the art as an "ABA triblock structure." The ratio of X / Y in the (meth)acrylic copolymer is preferably from (5 / 95) to (60 / 40), more preferably from (15 / 85) to (40 / 60).

[0020] In one embodiment, the (meth)acrylic copolymer molecule has an XY diblock structure. In the molecule of the XY diblock structure, the X block can be a region of 40% or less, 30% or less, or 25% or less from one end of the molecule (all repeating units contained in the molecule are taken as 100%). Here, the X block is the block on the side where alkoxysilyl groups are distributed in a relatively large amount.

[0021] In one embodiment, the (meth)acrylic copolymer molecule has an XYX triblock structure. In the XYX triblock structure molecule, the X block can be 40% or less, 30% or less, or 25% or less of the region from the end of the molecule (all repeating units contained in the molecule are taken as 100%). Here, the X block is a block located at both ends of the molecule.

[0022] The (meth)acrylic copolymer has a repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group. The repeating unit derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group is contained relatively in large amounts in the X block. The repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are more than 2.0 on average per molecule of the (meth)acrylic copolymer. When the (meth)acrylic copolymer has two or more X blocks in one molecule, the total number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the multiple X blocks is more than 2.0 on average. On the other hand, the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block are 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block.

[0023] The repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are on average more than 2.0 per molecule of the (meth)acrylic copolymer, preferably 2.1 or more, more preferably 2.2 or more, even more preferably 2.3 or more, and particularly preferably 2.5 or more. Similarly, the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are preferably 0.5% by weight or more, more preferably 2.0% by weight or more, and even more preferably 3.0% by weight or more based on the weight of all repeating units contained in the X block.

[0024] The upper limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is preferably 90% by weight or less, more preferably 60% by weight or less, and even more preferably 30% by weight or less. The upper limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is less than 5% by weight, preferably 4% by weight or less, more preferably 3% by weight or less, even more preferably 2% by weight or less, and particularly preferably 1% by weight or less, based on the weight of all repeating units contained in the Y block. The lower limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is preferably 0% by weight or more, and more preferably more than 0% by weight, based on the weight of all repeating units contained in the Y block.

[0025] Specific examples of (meth)acrylic acid ester monomers having an alkoxysilyl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0026] The (meth)acrylic copolymer may contain a repeating unit derived from a (meth)acrylic monomer having a long side chain. In this specification, the "(meth)acrylic monomer having a long side chain" refers to a repeating unit derived from a (meth)acrylic monomer having a long side chain, represented by the formula: R 1 CH=CHCOOR 2 In the formula, R 1 R is a hydrogen atom or a methyl group. 2 is a group having 9 or more carbon atoms.

[0027] The content of the repeating unit derived from the (meth)acrylic monomer having a long side chain is preferably 1% by weight or more of the total constitutional units contained in the (meth)acrylic copolymer. The (meth)acrylic copolymer containing such a repeating unit may have improved compatibility with the polyoxyalkylene polymer, or the physical properties of the resulting cured product may be improved. The upper limit of the content of the repeating unit derived from the (meth)acrylic monomer having a long side chain is preferably 5% by weight or less, more preferably 3% by weight or less, and even more preferably 1% by weight or less. If the content is within the above range, the production cost of the (meth)acrylic copolymer does not rise excessively.

[0028] Examples of (meth)acrylic monomers having a long side chain include nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, icosyl (meth)acrylate, docosyl (meth)acrylate, oleyl (meth)acrylate, linoleyl (meth)acrylate, and isobornyl (meth)acrylate.

[0029] Among the above-mentioned monomers, one or more selected from octadecyl (meth)acrylate, oleyl (meth)acrylate, and linoleyl (meth)acrylate are preferred. These monomers have the advantage of being liquid at room temperature and having high polymerization stability. In addition, by blending these monomers, a (meth)acrylic acid copolymer having high compatibility with a polyoxyalkylene polymer can be obtained.

[0030] In this specification, the term "(meth)acrylic monomer having a non-long side chain" refers to a (meth)acrylic monomer having a non-long side chain in the above formula, R 2 represents a monomer having 8 or less carbon atoms. Examples of such monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isopropoxyethyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, glycidyl (meth)acrylate, 1-ethylcyclopentyl ether (meth)acrylate, and dimethylaminoethyl (meth)acrylate.

[0031] Among the above-mentioned monomers, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred. These monomers have low procurement costs and are suitable for the purpose of reducing the production costs of the (meth)acrylic copolymer.

[0032] Furthermore, from the viewpoint of glass transition point, one or more selected from n-butyl acrylate and 2-ethylhexyl acrylate are preferred. The (meth)acrylic copolymer obtained from these monomers has a low glass transition point and a low polymer viscosity. Therefore, a curable composition that is easy to use in a low temperature environment can be obtained.

[0033] [2.1.2. Alkoxysilyl groups in (meth)acrylic copolymers] The (meth)acrylic copolymer has an alkoxysilyl group. The alkoxysilyl group of the (meth)acrylic copolymer may be derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group. In one embodiment, the alkoxysilyl group is represented by the following general formula: -[Si(R 4 ) 2-b (Y) b O] m -Si(R 5 ) 3-a (Y) a

[0034] In the formula, R 4 and R 5 are independently an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, a methoxymethyl group, or a triorganosiloxy group represented by (R')3SiO-. R' is a monovalent hydrocarbon group having 1 to 20 carbon atoms. The three R's may be the same or different. R 4 or R 5 When two or more are present, they may be the same or different. Y is an alkoxy group having 1 to 20 carbon atoms. When two or more Y are present, they may be the same or different. a is 0, 1, 2 or 3. b is 0, 1 or 2. m is an integer of 0 to 19, provided that the relationship a+mb≧1 is satisfied.

[0035] Generally, the fewer the carbon atoms in an alkoxy group, the higher its reactivity. In other words, the reactivity decreases in the order of methoxy group, ethoxy group, propoxy group, etc. Therefore, an appropriate alkoxy group can be selected depending on the production method and application of component (A).

[0036] The specific structure of the (meth)acrylic acid ester monomer having an alkoxysilyl group is not particularly limited. An example is a monomer represented by the following general formula: H2C=CR 6 C(=O)O-(CH2) m -SiR 7 n (OR 8 ) 3-n

[0037] In the formula, R 6 is hydrogen or a methyl group. 7 and R 8 R is at least one selected from the group consisting of hydrogen, a methyl group, and an ethyl group. 7 and / or R 8 When a plurality of are present, they may be the same or different. m is an integer of 0 to 10. n is an integer of 0 to 2.

[0038] Specific examples of the (meth)acrylic acid ester monomer having an alkoxysilyl group include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0039] The number of alkoxysilyl groups introduced into the (meth)acrylic copolymer is more than 2.0 on average, preferably 2.2 or more, more preferably 2.6 or more, even more preferably 3.0 or more, and particularly preferably 3.4 or more, in the whole molecule.The upper limit of the number of alkoxysilyl groups introduced into the (meth)acrylic copolymer is preferably 10.0 or less, more preferably 8.0 or less, even more preferably 6.0 or less, and particularly preferably 5.0 or less.When the number of alkoxysilyl groups is within the above range, a curable composition and a cured product with good physical properties can be obtained.

[0040] [2.1.3. Physical properties of (meth)acrylic copolymers] In one embodiment, the lower limit of the number average molecular weight of the (meth)acrylic copolymer is preferably 2,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more. The upper limit of the number average molecular weight of the (meth)acrylic copolymer is preferably 50,000 or less, more preferably 30,000 or less, and even more preferably 20,000 or less. When the number average molecular weight of the (meth)acrylic copolymer is in the above range, the viscosity of the curable composition does not become too high, and sufficient workability can be ensured.

[0041] In one embodiment, the molecular weight distribution of the (meth)acrylic copolymer is 1.8 or less, preferably 1.5 or less, 1.4 or less, 1.3 or less, or 1.2 or less. If the molecular weight distribution is within the above range, the viscosity of the polymer tends to decrease and the workability tends to improve. The molecular weight distribution is a value given by "weight average molecular weight ÷ number average molecular weight".

[0042] The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). For GPC measurement, chloroform is used as the mobile phase and a polystyrene gel column is used as the stationary phase. The molecular weight obtained by measurement is the molecular weight converted into standard polystyrene.

[0043] [2.1.4. Method for producing (meth)acrylic copolymer] The polymerization method of the (meth)acrylic copolymer is not particularly limited, and known polymerization methods can be used (radical polymerization method, cationic polymerization method, anionic polymerization method, etc.). The polymerization method called SGO (Solid Grade Oligomer; high temperature continuous bulk polymerization) is preferred because it is a method that can obtain a (meth)acrylic copolymer without using a polymerization solvent, a polymerization initiator, a chain transfer agent, etc. A living polymerization method is preferred because it can introduce a functional group near the end of the polymer molecule and can synthesize a (meth)acrylic copolymer with a small molecular weight distribution. Examples of living polymerization methods include living radical polymerization method, living cationic polymerization method, and living anionic polymerization method, and among them, living radical polymerization method is suitable for polymerization of a (meth)acrylic monomer. Examples of living radical polymerization methods include the following. Atom Transfer Radical Polymerization (ATRP) (see J. Am. Chem. Soc. 1995, 117, 5614; Macromolecules. 1995, 28, 1721) Single Electron Transfer Polymerization (SET-LRP (see J. Am. Chem. Soc. 2006, 128, 14156; JPSChem 2007, 45, 1607)) Reversible Chain Transfer Catalyzed Polymerization (RTCP) (see "Living Radical Polymerization Controlled by Organic Catalysts" Polymer Journal Vol. 68, 223-231 (2011); JP Patent Publication No. 2014-111798) Reversible addition-fragmentation chain transfer polymerization (RAFT polymerization) Nitroxy radical method (NMP method) Polymerization using organotellurium compounds (TERP method) · Polymerization method using organoantimony compounds (SBRP method) Polymerization method using organobismuth compounds (BIRP method) -Iodine transfer polymerization method

[0044] An example of a method for introducing a silyl group into a (meth)acrylic copolymer is the method described in JP 2018-162394 A. The method disclosed in the document introduces a silyl group into a (meth)acrylic copolymer by copolymerizing a (meth)acrylic acid ester monomer and a silyl group-containing (meth)acrylic acid ester monomer. More specifically, a silyl group is introduced near the end of a (meth)acrylic copolymer molecule by controlling the input amount of a silyl group-containing (meth)acrylic acid ester monomer according to the progress stage of living polymerization. The silyl group-containing (meth)acrylic copolymer obtained by these methods has a silyl group locally at or near the end of the molecule. The effect of achieving both strength and elongation of the curable composition is remarkably exhibited in a (meth)acrylic copolymer into which a silyl group has been introduced by such a method.

[0045] [2.2.(B) Compounds containing an amino group] The content of the (B) compound having an amino group is preferably 0.01 to 10 parts by weight, relative to 100 parts by weight of the total amount of the (A) (meth)acrylic copolymer having an alkoxysilyl group and the (E) polyoxyalkylene polymer having a silyl group.

[0046] In one embodiment, the compound comprises one or more amino groups and an organic group. The organic group is, for example, a functional group having 1 to 40 or 1 to 20 carbon atoms. The organic group may have a straight chain structure, a branched structure, or a ring. The organic group may have a double bond or a triple bond. The organic group may contain a heteroatom (oxygen, nitrogen, sulfur, phosphorus, halogen, etc.). In one embodiment, the compound comprises one or more amino groups and a hydrocarbon group. The hydrocarbon group is a functional group consisting of only carbon atoms and hydrogen atoms.

[0047] In this specification, an amino group is a functional group represented by -NH2. Substituted amino groups in which one or both of two hydrogen atoms are substituted are not included in the amino group in this specification. Therefore, the compound has a structure as a primary amine. The number of amino groups contained in the compound is not particularly limited. Therefore, the compound may be a monoamine or a polyamine (diamine, triamine, tetraamine, etc.).

[0048] Examples of the compound include aliphatic amines, alicyclic amines, and aromatic amines. More specific examples include monovalent aliphatic primary amines (butylamine, hexylamine, 2-ethylhexylamine, octylamine, laurylamine, stearylamine, tetradecylamine, pentadecylamine, 3-(diethylamino)propylamine, etc.); monovalent alicyclic primary amines (cyclohexylamine, cycloheptylamine, cyclooctylamine); monovalent aromatic primary amines (aniline, o-toluidine, benzylamine, etc.); polyvalent aliphatic primary amines (ethylenediamine, diethylenediamine, etc.); and polyvalent alicyclic primary amines (1,2-cyclohexyldiamine, 1,4-cyclohexyldiamine). The compound may also be a polymer having one or more amino groups.

[0049] [2.3.(C) Curing catalyst] The content of the (C) curing catalyst is preferably 0.1 to 5 parts by weight per 100 parts by weight of the total amount of the (A) alkoxysilyl group-containing (meth)acrylic copolymer and the (E) silyl group-containing polyoxyalkylene polymer.

[0050] Examples of the curing catalyst include tin-based curing catalysts. Specific examples of the tin-based curing catalyst include dialkyltin carboxylates (dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diethylhexanolate, dibutyltin dioctate, dibutyltin dimethyl maleate, dibutyltin diethyl maleate, dibutyltin dibutyl maleate, dibutyltin diisooctyl maleate, dibutyltin ditridecyl maleate, dibutyltin dibenzyl maleate, dibutyltin maleate, dioctyltin diacetate, dioctyltin distearate, dioctyltin dilaurate, dioctyltin diethyl maleate, dioctyltin diisooctyl maleate, etc.); dialkyltin oxides (dibutyltin oxide, dioctyltin oxide, a mixture of dibutyltin oxide and phthalic acid ester, etc.); tetravalent tin compounds (dialkyltin oxide, di ... Reaction products of tin diacetate, etc.) with low molecular weight silicon compounds having alkoxysilyl groups (tetraethoxysilane, methyltriethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, etc.); divalent tin compounds (tin octylate, tin naphthenate, tin stearate, etc.); monoalkyltin compounds (monobutyltin compounds (monobutyltin tris-octoate, monobutyltin triisopropoxide, etc.), monooctyltin compounds, etc.); chelate compounds (dibutyltin bisacetylacetonate, dioctyltin bisacetylcetonate, dibutyltin bisethylacetonate, dioctyltin bisethylacetonate, etc.); tin alcoholates (dibutyltin dimethylate, dibutyltin diethylate, dioctyltin dimethylate, dioctyltin diethylate, etc.).

[0051] [2.4.(D) Phosphate esters] By incorporating a phosphoric acid ester, the storage stability of the curable composition is improved, for example, the viscosity increase rate of the curable composition after storage is reduced.

[0052] The content of (D) the phosphoric acid ester is preferably 0.01 to 10 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0053] A phosphate ester is a compound represented by O=P(OR)3. Each of the three R's is independently selected from an organic group or a hydrogen atom. The organic group is, for example, a functional group having 1 to 40 or 1 to 20 carbon atoms. A compound in which two R's are hydrogen atoms is called a phosphate monoester, a compound in which one R's is a hydrogen atom is called a phosphate diester, and a compound in which no R's are hydrogen atoms is called a phosphate triester.

[0054] Examples of phosphoric acid monoesters include monomethyl phosphate, monoethyl phosphate, mono-n-propyl phosphate, monoisopropyl phosphate, mono-n-butyl phosphate, mono(2-ethylhexyl) phosphate, monolauryl phosphate, phenyl phosphate, cresyl phosphate, xylenyl phosphate, and benzyl phosphate. Examples of phosphoric acid diesters include dimethyl phosphate, diethyl phosphate, di-n-propyl phosphate, diisopropyl phosphate, di-n-butyl phosphate, bis(2-ethylhexyl) phosphate, dilauryl phosphate, diphenyl phosphate, dicresyl phosphate, dixylenyl phosphate, and dibenzyl phosphate. Examples of phosphoric acid triesters include trimethyl phosphate, triethyl phosphate, tri-n-propyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, tri(2-ethylhexyl) phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, and tribenzyl phosphate. Among the phosphoric acid esters, phosphoric acid monoesters and phosphoric acid diesters are preferred. This is because these phosphoric acid esters have a suitable balance between acidity and viscosity.

[0055] [2.5. (E) Polyoxyalkylene polymer having silyl group] The lower limit of the content of the polyoxyalkylene polymer having a silyl group (E) is preferably 5 parts by weight or more, more preferably 30 parts by weight or more, and even more preferably 40 parts by weight or more, when the content of the (meth)acrylic copolymer having an alkoxysilyl group (A) is 100 parts by weight. The upper limit of the content of the polyoxyalkylene polymer having a silyl group (E) is preferably 300 parts by weight or less, more preferably 280 parts by weight or less, and even more preferably 250 parts by weight or less, when the content of the (meth)acrylic copolymer having an alkoxysilyl group (A) is 100 parts by weight. If the content ratio of the (meth)acrylic copolymer having an alkoxysilyl group (A) and the polyoxyalkylene polymer having a silyl group (E) is within the above range, a cured product with excellent weather resistance can be obtained. In order to ensure weather resistance for a longer period of time, it is preferable to contain more of the (meth)acrylic copolymer having an alkoxysilyl group (A) than the polyoxyalkylene polymer having a silyl group (E).

[0056] [2.5.1. Main chain of polyoxyalkylene polymer] The molecular structure of the polyoxyalkylene polymer may be linear or branched. It may also be a mixture of molecules having these structures. Among these, the main chain derived from one or more selected from the group consisting of polyoxypropylene diol and polyoxypropylene triol is particularly preferred.

[0057] Examples of the main chain structure of the polyoxyalkylene polymer include a structure represented by the following general formula: 9 is a divalent alkylene group. -R 9 -O-

[0058] The repeating units described above preferably account for 50% by weight or more of the total weight of the polyoxyalkylene polymer, more preferably 70% by weight or more, and even more preferably 90% by weight or more.

[0059] R 9 The structure of R is not particularly limited as long as it is a divalent alkylene group.9 is preferably an alkylene group having 1 to 14 carbon atoms, and more preferably a linear or branched alkylene group having 2 to 4 carbon atoms.

[0060] Specific examples of the repeating unit include -CH2O-, -CH2CH2O-, -CH2CH(CH3)O-, -CH2CH(C2H5)O-, -CH2C(CH3)2O-, and -CH2CH2CH2CH2O-. Among these, it is preferable that the main chain of the polyoxyalkylene polymer is polypropylene oxide consisting of -CH2CH(CH3)O-.

[0061] The main chain structure of the polyoxyalkylene polymer may be a commercially available product. Examples of commercially available polyoxyalkylene polymers include Kaneka MS Polymer (registered trademark) S810, S257, S327 (all Kaneka Corporation); Silyl (registered trademark) SAX220, SAT400, SAX510, SAX520, SAX580, SAX750, SAT145 (all Kaneka Corporation); Exestar (registered trademark) ES-S2410, ES-S2420, ES-S3630 (all AGC Corporation); and HMS-1603, HMS-1207 (all Hua Ma Technology).

[0062] [2.5.2. Silyl group possessed by polyoxyalkylene polymer] The structure of the silyl group contained in the polyoxyalkylene polymer is not particularly limited. The silyl group contained in the polyoxyalkylene polymer may be the alkoxysilyl group contained in the (meth)acrylic copolymer described in Section [2.1.2.].

[0063] In one embodiment, the structure of the silyl group contained in the polyoxyalkylene polymer is represented by the following formula. -Si(R 3 ) 3-a (X) a

[0064] In the formula, one silyl group is R 3When multiple R are included, they may be the same or different. 3 R represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms. 3 When R is substituted, it may be substituted with a heteroatom-containing group. When multiple silyl groups are present, R 3 may be different for each silyl group. 3 Examples of X include an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms. When one silyl group contains a plurality of Xs, they may be the same or different. X represents a hydroxyl group or a hydrolyzable group. When a plurality of silyl groups are present, X may be different for each silyl group. An example of the hydrolyzable group is an alkoxy group. a is 1, 2, or 3.

[0065] Examples of the silyl group contained in the polyoxyalkylene polymer include a dimethoxysilyl group, a trimethoxysilyl group, a diethoxysilyl group, a triethoxysilyl group, a triisopropoxysilyl group, a dimethoxymethylsilyl group, a diethoxymethylsilyl group, and a diisopropoxymethylsilyl group.

[0066] The number of silyl groups introduced into the polyoxyalkylene polymer is preferably more than 1.2 per molecule, more preferably 1.2 to 4.0, and even more preferably 1.5 to 2.5. When the number of silyl groups is within the above range, good curability can be imparted to the curable composition.

[0067] In addition to the above, it is also possible to use a polyalkylene polymer having only one silyl group at the end. When used in combination with the above polymer, it is possible to replace the plasticizer component. Furthermore, it is possible to use a polyalkylene polymer obtained by the synthesis method described in JP 2021-75722 A.

[0068] The silyl group of the polyoxyalkylene polymer is preferably located at at least one end of the molecule, and more preferably located at both ends of the molecule. If the silyl group is located at the end of the molecule, good elongation can be imparted to the cured product.

[0069] [2.5.3. Other physical properties of polyoxyalkylene polymers] The lower limit of the number average molecular weight of the polyoxyalkylene polymer is not particularly limited, and is preferably 3,000 or more, more preferably 10,000 or more, and even more preferably 20,000 or more. The upper limit of the number average molecular weight of the polyoxyalkylene polymer is preferably 70,000 or less, and more preferably 50,000 or less. By using a high molecular weight polymer having a number average molecular weight of 20,000 or more as the polyoxyalkylene polymer, the elongation of the cured product can be improved.

[0070] The molecular weight distribution of the polyoxyalkylene polymer is preferably 1.6 or less, more preferably 1.5 or less, and further preferably 1.2 or less. If the molecular weight distribution is too large, the viscosity of the curable composition increases, and the workability tends to decrease.

[0071] Such a polyoxyalkylene polymer can be obtained by the method described in

[0011] to

[0058] of JP2021-55010A.

[0072] [2.6. Other ingredients] The curable composition may contain various additives in addition to the above-mentioned components. By adding these additives, various physical properties of the curable composition and the cured product can be adjusted. Examples of additives include the following.

[0073] (Adhesion promoter) The curable composition may contain an adhesion promoter. By adding an adhesion promoter, the risk of the sealant peeling off from the adherend such as a siding board can be reduced (this peeling occurs when the joint width changes due to an external force). In addition, there may be cases where the need to use a primer to improve adhesion is eliminated. In this case, simplification of the construction work is expected.

[0074] An example of an adhesion promoter is a silane coupling agent. Specific examples of silane coupling agents include isocyanate group-containing silanes (γ-isocyanate propyl trimethoxysilane, γ-isocyanate propyl triethoxysilane, γ-isocyanate propyl methyl diethoxysilane, γ-isocyanate propyl methyl dimethoxysilane, etc.); amino group-containing silanes (γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl methyl diethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl diethoxysilane, γ-ureidopropyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, N-benzyl-γ-aminopropyl trimethoxysilane, silane, N-vinylbenzyl-γ-aminopropyltriethoxysilane, etc.); mercapto group-containing silanes (γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane, etc.); carboxysilanes (β-carboxyethyltriethoxysilane, β-carboxyethylphenylbis(2-methoxyethoxy)silane, N-(β-carboxymethyl)aminoethyl-γ-aminopropyltrimethoxysilane, etc.); vinyl-type unsaturated group-containing silanes (vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloyloxypropylmethyldimethoxysilane, γ-acroyloxypropylmethyltriethoxysilane, etc.); halogen-containing silanes (γ-chloropropyltrimethoxysilane, etc.); isocyanurate silanes (tris(trimethoxysilyl)isocyanurate, etc.).In addition, derivatives obtained by modifying silane coupling agents, such as amino-modified silyl polymers, silylated amino polymers, unsaturated aminosilane complexes, phenylamino long-chain alkylsilanes, aminosilylated silicones, and silylated polyesters, can also be used as silane coupling agents.

[0075] The content of the adhesion promoter is preferably 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0076] (filling material) The curable composition may contain a filler. Examples of the filler include wood flour, reinforcing fillers (pulp, cotton chips, asbestos, mica, walnut shell powder, rice husk powder, graphite, white clay, silica (fumed silica, precipitated silica, crystalline silica, fused silica, dolomite, silicic anhydride, hydrated silicic acid, etc.), carbon black, etc.), fillers (heavy calcium carbonate, colloidal calcium carbonate, magnesium carbonate, diatomaceous earth, calcined clay, clay, talc, titanium oxide, bentonite, organic bentonite, ferric oxide, red iron oxide, fine aluminum powder, flint powder, zinc oxide, activated zinc oxide, zinc powder, zinc carbonate, shirasu balloon, etc.), and fibrous fillers (asbestos, glass fiber and glass filament, carbon fiber, Kevlar fiber, polyethylene fiber, etc.).

[0077] The content of the filler is preferably 5 to 5,000 parts by weight, more preferably 10 to 2,500 parts by weight, and particularly preferably 15 to 1,500 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0078] (Plasticizer) The curable composition may contain a plasticizer. The use of a plasticizer in combination with a filler increases the elongation of the cured product and allows the incorporation of a large amount of filler.

[0079] Examples of plasticizers include phthalates (dibutyl phthalate, diheptyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate, butyl benzyl phthalate, etc.); non-aromatic dibasic acid esters (dioctyl adipate, dioctyl sebacate, dibutyl sebacate, isodecyl succinate, etc.); aliphatic esters (butyl oleate, methyl acetylricinoleate, etc.); esters of polyalkylene glycols (diethylene glycol dibenzoate, triethylene glycol dibenzoate, pentaerythritol esters, etc.); phosphate esters (tricresyl phosphate, tributyl phosphate, etc.); trimellitic acid esters, polystyrenes (polystyrene, poly-α-methylstyrene, etc.); polybutadiene; polybutene; polyisobutylene; butadiene. Examples of suitable plasticizers include diene-acrylonitrile, polychloroprene, chlorinated paraffins, hydrocarbon oils (alkyldiphenyls, partially hydrogenated terphenyls, etc.), process oils, polyethers (polyether polyols (polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.), and derivatives in which the hydroxyl groups of polyether polyols are converted to ester groups, ether groups, etc.), polyester plasticizers obtained from dibasic acids and dihydric alcohols (polyesters obtained from sebacic acid, adipic acid, azelaic acid, phthalic acid, etc., and ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, etc.), and vinyl polymers (obtained by polymerizing vinyl monomers such as acrylic plasticizers by various methods).

[0080] Acrylic plasticizers can be produced by high-temperature continuous polymerization without using solvents and chain transfer agents (see U.S. Pat. No. 4,414,370, JP-A-59-6207, JP-B-5-58005, JP-A-1-313522, and U.S. Pat. No. 5,010,166). Specific examples of acrylic plasticizers include ARUFON UP-1000, UP-1020, and UP-1110 (all from Toagosei Co., Ltd.), JDX-P1000, JDX-P1010, and JDX-P1020 (all from Johnson Polymer Co., Ltd.).

[0081] The content of the plasticizer is preferably 5 to 800 parts by weight, more preferably 10 to 600 parts by weight, and even more preferably 10 to 500 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0082] (Physical property adjuster) The curable composition may contain a physical property modifier that adjusts the tensile properties of the cured product. By using the physical property modifier, it is possible to increase the hardness of the cured product, or conversely, to decrease the hardness of the cured product and increase the elongation.

[0083] Examples of physical property adjusters include alkylalkoxysilanes (methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, n-propyltrimethoxysilane, etc.); alkylisopropenoxysilanes (dimethyldiisopropenoxysilane, methyltriisopropenoxysilane, etc.); alkoxysilanes having functional groups (vinyldimethylmethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)aminopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, etc.); silicone varnishes; and polysiloxanes.

[0084] The content of the physical property adjusting agent is preferably 0.1 to 80 parts by weight, and more preferably 0.1 to 50 parts by weight, per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0085] (Thixotropic agent (anti-sagging agent)) The curable composition may contain a thixotropic agent (anti-sagging agent) to prevent sagging and improve workability.

[0086] Examples of the thixotropic agent include polyamide waxes; hydrogenated castor oil derivatives; and metal soaps (calcium stearate, aluminum stearate, barium stearate, etc.).

[0087] The content of the thixotropy-imparting agent is preferably 0.1 to 50 parts by weight, and more preferably 0.2 to 25 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0088] (light curing substance) The curable composition may contain a photocurable substance. A photocurable substance is a substance that undergoes a chemical change in a short time by the action of light, resulting in a change in physical properties (such as curing). By including a photocurable substance, the tackiness (residual tack) of the surface of the cured product can be reduced. A typical photocurable substance can be cured by leaving it at room temperature for one day in a sunny position indoors (such as near a window). Many photocurable substances are known, such as organic monomers, oligomers, resins, and compositions containing these, and the types are not particularly limited. Examples of photocurable substances include unsaturated acrylic compounds, polyvinyl cinnamates, and azido resins.

[0089] Specific examples of unsaturated acrylic compounds include (meth)acrylic acid esters of low molecular weight alcohols (ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, neopentyl alcohol, etc.); (meth)acrylic acid esters of alcohols obtained by modifying acids (bisphenol A, isocyanuric acid) or low molecular weight alcohols with ethylene oxide, propylene oxide, etc.; (meth)acrylic acid esters (polyether polyols whose main chain is polyether and has hydroxyl groups at the terminals, and vinyl monomers radically polymerized in polyols whose main chain is polyether). polymer polyols obtained by reacting an epoxy resin (such as bisphenol A type or novolak type) with (meth)acrylic acid, polyester polyols having a polyester main chain and hydroxyl groups at the terminals, and polyols having a vinyl or (meth)acrylic copolymer main chain and hydroxyl groups in the main chain; epoxy acrylate oligomers obtained by reacting an epoxy resin (such as bisphenol A type or novolak type) with (meth)acrylic acid; and urethane acrylate oligomers having urethane bonds and (meth)acrylic groups in the molecular chain obtained by reacting a polyol, a polyisocyanate, a hydroxyl group-containing (meth)acrylate, etc.

[0090] The content of the photocurable substance is preferably 0.01 to 30 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0091] (Air oxidation curing substance) The curable composition may contain an air-oxidation curing substance. An air-oxidation curing substance is a substance having an unsaturated group that can be crosslinked and cured by oxygen in the air. By including an air-oxidation curing substance, the tackiness (residual tack) of the surface of the cured product can be reduced. A typical air-oxidation curing substance can be cured by leaving it to stand in the air indoors for one day, for example.

[0092] Examples of air-oxidative curing substances include drying oils (tung oil, linseed oil, etc.); various alkyd resins obtained by modifying drying oils; substances obtained by modifying acrylic polymers, silicone resins, etc. with drying oils; 1,2-polybutadiene; 1,4-polybutadiene; polymers or copolymers of C5-C8 dienes; various modified products of polymers or copolymers of C5-C8 dienes (malein modified products, boiled oil modified products, etc.). Among the above, tung oil, liquid diene polymers, and modified products thereof are preferred.

[0093] The amount of the air oxidative curing substance is preferably 0.01 to 30 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0094] (Antioxidants and Light Stabilizers) The curable composition may contain an antioxidant and / or a light stabilizer. Various antioxidants and light stabilizers are known. For example, the substances described in [Kenichi Saruwatari et al., "Antioxidant Handbook," Taiseisha, 1976] and [Zenjiro Osawa, editor, "Deterioration and Stabilization of Polymer Materials," CMC, 1990, pp. 235-242] can be mentioned.

[0095] Examples of the antioxidant include thioether-based antioxidants such as ADK STAB PEP-36 and ADK STAB AO-23 (all manufactured by ADEKA Corporation); phosphorus-based antioxidants such as Irgafos38, Irgafos168, and IrgafosP-EPQ (all manufactured by Ciba Specialty Chemicals); and hindered phenol-based antioxidants. Among the above, hindered phenol-based antioxidants are preferred.

[0096] Specific examples of hindered phenol-based antioxidants include 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-ethylphenol, mono (or di or tri) (α-methylbenzyl)phenol, 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), and 2,5-di-t-butylhydroquinone. , 2,5-di-t-amylhydroquinone, triethylene glycol-bis-[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylene 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-t-butyl-4-hydroxybenzyl)propionate, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 3,5-di-t-butyl-4-hydroxy-benzylphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-t-butyl-4-hydroxybenzyl)propionate ethyl benzylphosphonate) calcium, tris-(3,5-di-t-butyl-4-hydroxybenzyl) isocyanurate, 2,4-bis[(octylthio)methyl]o-cresol, N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine, tris(2,4-di-t-butylphenyl)phosphite, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3,5-di-t-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)-benzotriazole, methyl-3-[3-t-bu ethyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate-polyethylene glycol (molecular weight about 300) condensate, hydroxyphenylbenzotriazole derivatives, 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl), 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate.

[0097] Examples of commercially available antioxidants include Nocrac 200, Nocrac M-17, Nocrac SP, Nocrac SP-N, Nocrac NS-5, Nocrac NS-6, Nocrac NS-30, Nocrac 300, Nocrac NS-7, and Nocrac DAH (all manufactured by Ouchi Shinko Chemical Industry Co., Ltd.); ADK STAB AO-30, ADK STAB AO-40, ADK STAB AO-50, ADK STAB AO-60, ADK STAB AO-616, ADK STAB AO-635, ADK STAB AO-658, ADK STAB AO-80, ADK STAB AO-15, ADK STAB AO-18, ADK STAB 328, and ADK STAB AO-37 (all manufactured by ADEKA Corporation); IRGANOX-245, IRGANOX-259, IRGANOX-565, IRGANOX-1010, IRGANOX-1024, IRGANOX-1035, IRGANOX-1076, IRGANOX-1081, IRGANOX-1098, IRGANOX-1222, IRGANOX-1330, IRGANOX-1425WL (all manufactured by Chiba Specialty Chemicals); Sumilizer GM, Sumilizer GA-80, Sumilizer GS (all manufactured by Sumitomo Chemical Co., Ltd.).

[0098] Examples of light stabilizers include ultraviolet absorbers (benzotriazole compounds such as Tinuvin P, Tinuvin 234, Tinuvin 320, Tinuvin 326, Tinuvin 327, Tinuvin 329, and Tinuvin 213 (all manufactured by Ciba Specialty Chemicals); triazine light stabilizers such as Tinuvin 1577; benzophenone compounds such as CHIMASSORB81; benzoate compounds such as Tinuvin 120 (manufactured by Ciba Specialty Chemicals); and hindered amine compounds). Of the above, hindered amine compounds are preferred.

[0099] Specific examples of the hindered amine compound include dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}], N,N'-bis(3aminopropyl)ethylenediamine-2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, and bis(2,2,6,6-tetramethyl-4-piperidinyl)succinate.

[0100] Examples of commercially available light stabilizers include Tinuvin 622LD, Tinuvin 144, CHIMASSORB944LD, and CHIMASSORB119FL (all manufactured by Chiba Specialty Chemicals), Adeka STAB LA-52, Adeka STAB LA-57, Adeka STAB LA-62, Adeka STAB LA-67, Adeka STAB LA-63, Adeka STAB LA-68, Adeka STAB LA-82, and Adeka STAB LA-87 (manufactured by ADEKA Corporation); Sanol LS-770, Sanol LS-765, Sanol LS-292, Sanol LS-2626, Sanol LS-1114, Sanol LS-744, and Sanol LS-440 (manufactured by Chiba Specialty Chemicals).

[0101] An antioxidant and a light stabilizer may be used in combination. By using them in combination, the effect of each agent may be further improved, and the heat resistance, weather resistance, etc. of the cured product may be improved. For example, in order to improve weather resistance, an ultraviolet absorber and a hindered amine compound (HALS) may be combined. This combination is preferable because it can further improve the effect of each agent.

[0102] The content of the antioxidant and / or light stabilizer is preferably 0.1 to 20 parts by weight, based on 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0103] [3. Summary] The present invention includes the following aspects. <1> A method for producing a curable composition, comprising the steps of: Step (1): (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) a compound having an amino group are mixed together; Step (2): adding a curing catalyst (C) to the mixture obtained in step (1); The (A) (meth)acrylic copolymer having an alkoxysilyl group has a molecular weight distribution (Mw / Mn) of 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, the number of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, A production method in which the repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block. <2> The (A) (meth)acrylic copolymer having an alkoxysilyl group is R 1 CH=CHCOOR 2 Contains 1% by weight or more of repeating units derived from In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 is a group having 9 or more carbon atoms, <1> A method for producing the curable composition according to claim 1. <3> The number average molecular weight of the (A) (meth)acrylic copolymer having an alkoxysilyl group is 2,000 or more and 50,000 or less. <1> or <2> A method for producing the curable composition according to claim 1. <4> In the above step (1), (D) a phosphoric acid ester is further mixed. <1> ~ <3> 13. A method for producing the curable composition according to any one of claims 1 to 12. <5> In the above step (1), (E) a polyoxyalkylene polymer having a silyl group is further mixed. <1> ~ <4> 13. A method for producing the curable composition according to any one of claims 1 to 12. <6> The silyl group of the (E) polyoxyalkylene polymer having a silyl group is represented by the formula: -Si(R 3 )3-a (X) a Represented by <5> A method for producing the curable composition according to the present invention comprising the steps of: During the ceremony, R 3 represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms; R 3 may be substituted with a heteroatom-containing group; R in one silyl group 3 When multiple are included, they may be the same or different; R 3 may be different for each silyl group; X represents a hydroxyl group or a hydrolyzable group; When one silyl group contains a plurality of X's, they may be the same or different. X may be different for each silyl group; a is 1, 2 or 3. <7> The number average molecular weight of the (E) polyoxyalkylene polymer having a silyl group is 3,000 or more and 50,000 or less. <5> or <6> A method for producing the curable composition according to claim 1. <8> <1> ~ <7> 2. A method for producing a cured product, comprising: curing a curable composition obtained by any one of the methods described above. EXAMPLES

[0104] [Measurement method] [Number average molecular weight and weight average molecular weight] The following devices were used to measure the number average molecular weight and the weight average molecular weight. The measured values ​​are polystyrene-equivalent molecular weights. Liquid delivery system: HLC-8120GPC (Tosoh Corporation) Column: TSK-GEL H type (Tosoh Corporation) Solvent: THF

[0105] [Molecular weight distribution] The molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0106] [Terminal silyl group introduction rate] 1 The introduction rate of terminal silyl groups was calculated from the results of H-NMR measurement. 1 The following equipment was used for H-NMR measurements. Measuring instrument: JNM-LA400 (JEOL Ltd.) Solvent: CDCl3

[0107] [Viscosity and thickening rate] The viscosity of the curable composition was measured in accordance with JIS K 7117-2 immediately after preparation, after storage at 50°C for 1 week, and after storage at 50°C for 2 weeks. The viscometer used was TVE-25L (Toki Sangyo Co., Ltd.). The cone rotor used was R14. The rotation speed of the cone rotor was 1 rpm. The measurement temperature was 23°C. The amount of sample used in the measurement was 0.4 mL.

[0108] The viscosity increase rate after one week or two weeks was calculated using the following formula. Viscosity increase rate after 1 week = viscosity after 1 week storage ÷ viscosity immediately after preparation Viscosity increase rate after 2 weeks = Viscosity after 2 weeks of storage ÷ Viscosity immediately after preparation

[0109] [Tensile properties] The tensile properties were measured by cutting No. 3 dumbbell-shaped test pieces from the cured products in accordance with JIS K 6251. The tensile properties were measured at 23°C and 55% RH using an autograph. The evaluation items were the stress at 100% elongation, the stress at break, and the elongation at break.

[0110] [Tear strength] A crescent-shaped test piece was obtained from the cured product, and the tear strength was measured in accordance with JIS K 6252. The tear strength was measured using an autograph at 23°C and 55% RH.

[0111] 〔material〕 The following materials were used: (A) (Meth)acrylic copolymer having an alkoxysilyl group Silyl group-containing (meth)acrylic copolymer (A-1) obtained in the production example (B) Compounds containing an amino group Amino compound (B-1): Hexylamine (Tokyo Chemical Industry Co., Ltd.) Amino compound (B-2): Laurylamine (Tokyo Chemical Industry Co., Ltd.) Amino compound (B-3): Modified aliphatic polyamine (FXJ-8074-D, T&K TOKA Corporation) ●(C) Curing catalyst Curing catalyst (C): Dibutyltin (Neostan U-220H, Nitto Kasei Co., Ltd.) (D) Phosphate ester Phosphate ester (D-1): Methyl acid phosphate (AP-1, Daihachi Chemical Industry Co., Ltd.) Phosphate ester (D-2): 2-ethylhexyl acid phosphate (AP-8, Daihachi Chemical Industry Co., Ltd.) Phosphate ester (D-3): Dibutyl phosphate (DP-4, Daihachi Chemical Industry Co., Ltd.) Dehydrating agent Vinyltrimethoxysilane (Silquest A-171, MOMENTIVE) Adhesion enhancer N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (KBM-603, Shin-Etsu Chemical Co., Ltd.)

[0112] [Production Example: Synthesis of Silyl Group-Containing (Meth)acrylic Copolymer (A-1)] A silyl group-containing (meth)acrylic copolymer (A-1) was synthesized by the following procedure. This copolymer satisfies the requirements for (A) a (meth)acrylic copolymer having an alkoxysilyl group. [Preparation] 1. A 2000 mL three-neck flask was prepared. 108 g of ethyl acrylate, 707 g of n-butyl acrylate, and 186 g of octadecyl acrylate were charged into the flask and mixed. This mixture is referred to as "(meth)acrylic acid ester monomer mixture." 2. Another stirring vessel was prepared. 52.7 mg of cupric bromide (CuBr2), 54.4 mg of hexamethyltris(2-aminoethyl)amine (Me6TREN) and 1.82 g of methanol were charged into the stirring vessel and stirred under a nitrogen stream until a homogeneous solution was obtained. This homogeneous solution is referred to as the "copper solution." The amount of copper contained in the copper solution was equivalent to 15 ppm relative to the total amount of the (meth)acrylic acid ester monomer mixture. 3. Another stirring vessel was prepared. 30.8 mL of methanol, 1.0 g of ascorbic acid, and 1.6 mL of triethylamine were charged into the stirring vessel and stirred under a nitrogen stream to obtain a homogeneous solution. This homogeneous solution is called "ascorbic acid solution." [1st step] 4. 5.60g of ethyl α-bromobutyrate (initiator; 0.029 mol), 20% by weight of the total amount of (meth)acrylic acid ester monomer mixture, 10g of 3-methacryloxypropylmethyldimethoxysilane (0.045 mol; 1.5 molar equivalent to the initiator), 107.68g of methanol, and the total amount of copper solution were added to the stirrer, and stirred for 30 minutes under a nitrogen stream to obtain a homogeneous solution. The stirrer used at this time was a stirrer with a jacket temperature control, and the jacket temperature was set to 45°C. 5. When the temperature in the polymerization system reached 40°C or higher, the ascorbic acid solution was continuously dripped to start the polymerization reaction. The dripping rate of the ascorbic acid solution was set to a rate at which 144 mg of ascorbic acid was added to the polymerization system per hour. 6. The temperature in the polymerization system was monitored and it rose as soon as the dropping of ascorbic acid started, reached a maximum temperature, and then gradually decreased. When the temperature difference between the temperature in the polymerization system and the jacket temperature reached 1°C, a small amount of the reaction solution in the polymerization system was sampled and analyzed by gas chromatography. As a result, 90% by weight of the (meth)acrylic acid ester monomer mixture initially charged had been consumed. [Second process] 7. The remaining (meth)acrylic acid ester monomer mixture that was not added in the first step (80% by weight of the total amount) was continuously added dropwise to the polymerization system over a period of 90 minutes. The ascorbic acid solution was added dropwise at a rate of 48 mg of ascorbic acid per hour to the polymerization system. Sampling was also carried out sequentially and analyzed by gas chromatography. The polymerization was continued until 88% by weight of the total (meth)acrylic acid ester monomer mixture added to the polymerization system was consumed. [3rd step] 8. 11 g of 3-methacryloxypropylmethyldimethoxysilane (0.049 mol; 1.6 molar equivalents relative to the initiator) was added to the polymerization system. The ascorbic acid solution was continuously added dropwise until 98% by weight of the total amount of the (meth)acrylic acid ester monomer mixture added to the polymerization system was consumed. Thereafter, the addition of the ascorbic acid solution was stopped to terminate the polymerization. 9. The jacket temperature was changed to 80°C, and the solvent was then volatilized. A diaphragm pump was used first, and then a vacuum pump was used. After volatilization was completed, the jacket temperature was cooled to 60°C or less. [purification] 10. 1000g of butyl acetate was added to a jacket temperature-controlled stirring device and mixed with the polymer after devolatilization until a homogeneous solution was obtained. An adsorbent was added to this homogeneous solution and stirred for 1 hour. As the adsorbent, 10g of Kyoward 500SH (Kyowa Chemical Industry Co., Ltd.) and 10g of Kyoward 700SEN-S (Kyowa Chemical Industry Co., Ltd.) were used. 11. After the stirring was completed, the mixture was filtered through a filter equipped with a bag filter cloth. This resulted in a clear polymer solution. 1.5 g of an antioxidant (Sumilizer GS; Sumitomo Chemical Co., Ltd.) was added to the solution and mixed until homogenous. Thereafter, the solvent was removed from the solution using a diaphragm pump first and then a vacuum pump. In this way, a (meth)acrylic copolymer (A-1) was obtained.

[0113] The (meth)acrylic copolymer (A-1) was an XYX type block copolymer, with a number average molecular weight of 5,5000, a molecular weight distribution of 1.11, and a number of silyl groups introduced per molecule of 2.1. The X block of the (meth)acrylic copolymer (A-1) had an average of 2.1 repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group per copolymer molecule. The Y block of the (meth)acrylic copolymer (A-1) had 1.1% by weight of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group (based on the weight of all repeating units contained in the Y block). The repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block were extremely small. Therefore, when calculated with two significant digits, the number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the entire molecule, and the number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the entire X block are both 2.1.

[0114] [Examples 1 to 6, Comparative Examples 1 and 2] A cured product was prepared according to the following procedure. 1. Prepare each component in the amount (unit: g) shown in Table 1. 2. These ingredients were added to a 150cc plastic cup and mixed using a spoon after each addition. The ingredients were added to the cup in one of the following orders: ●Order A (A) (Meth)acrylic polymer having an alkoxysilyl group (B) Compounds having an amino group and a moiety with six or more carbon atoms (if contained) (D) Phosphate esters (if contained) Dehydrating agent Adhesion promoter ·(C) Curing catalyst ●Order B (A) (Meth)acrylic polymer having an alkoxysilyl group Dehydrating agent Adhesion promoter ·(C) Curing catalyst (B) Compounds having an amino group and a moiety with six or more carbon atoms connected thereto 3. Using a planetary stirring and degassing device (ARE-310, Thinky Corporation), the mixture was stirred (1600 rpm x 90 seconds) and degassed (2200 rpm x 300 seconds) to obtain a curable composition. 4. The obtained curable composition was cured under conditions of 23°C and 50% RH to obtain a cured product.

[0115] 〔result〕 The results are shown in Table 1. [Table 1]

[0116] As can be seen from Table 1, in the examples, the curable compositions were obtained by a production method having two steps, namely, a step of mixing (A) an alkoxysilyl group-containing (meth)acrylic polymer and (B) an amino group-containing compound, and then a step of adding (C) a curing catalyst and further mixing. In Comparative Example 1, the amino group-containing compound (B) was not blended, so the curable composition was prepared by a production method not having these steps.

[0117] When comparing the strength of the cured products, the cured products of the Examples had the same or higher stress at 100% elongation and tear strength as the cured products of the Comparative Examples. When comparing the elongation of the cured products, the cured products of the Examples had significantly higher elongation at break than the cured products of the Comparative Examples. These results show that the cured products of the Examples have both high levels of elongation and strength.

[0118] As can be seen from Comparative Example 2, when the composition was prepared without mixing (B) the compound having an amino group before (C) the curing catalyst, curing started immediately after mixing, and mechanical strength could not be measured. This shows that the mixing order of (B) the compound having an amino group and (C) the curing catalyst is important in order to obtain a cured product that has both elongation and strength.

[0119] Furthermore, when Examples 1 to 3 are compared with Examples 4 to 6, it is found that the storage stability of the curable composition is further improved by adding the (D) phosphoric ester. [Industrial Applicability]

[0120] The curable composition obtained by the production method according to one embodiment of the present invention can be suitably used as a pressure-sensitive adhesive, a sealing material, an adhesive, a mold release agent, an anti-vibration material, a vibration-damping material, a soundproofing material, a foam material, a paint, a spray material, etc.

Claims

1. A method for producing a curable composition, comprising the steps of: Step (1): A step of mixing (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) a compound having an amino group; Step (2): adding a curing catalyst (C) to the mixture obtained in the step (1); The molecular weight distribution (Mw / Mn) of the (A) (meth)acrylic copolymer having an alkoxysilyl group is 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, the number of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, A production method in which the repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block.

2. The (A) (meth)acrylic copolymer having an alkoxysilyl group is R 1 CH=CHCOOR 2 Contains 1% by weight or more of repeating units derived from In the formula, R 1 is a hydrogen atom or a methyl group, R 2 The method for producing a curable composition according to claim 1 , wherein is a group having 9 or more carbon atoms.

3. The method for producing a curable composition according to claim 1, wherein the (A) (meth)acrylic copolymer having an alkoxysilyl group has a number average molecular weight of 2,000 or more and 50,000 or less.

4. The method for producing a curable composition according to claim 1 , wherein in the step (1), (D) a phosphoric acid ester is further mixed.

5. The method for producing a curable composition according to claim 1, wherein in the step (1), (E) a polyoxyalkylene polymer having a silyl group is further mixed.

6. The silyl group of the (E) polyoxyalkylene polymer having a silyl group is represented by the formula: -Si(R 3 ) 3-a (X) a A method for producing the curable composition according to claim 5, represented by the formula: During the ceremony, R 3 represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms; R 3 may be substituted with a heteroatom-containing group; One silyl group has R 3 When multiple are included, they may be the same or different; R 3 may be different for each silyl group; X represents a hydroxyl group or a hydrolyzable group; When one silyl group contains a plurality of X's, they may be the same or different. X may be different for each silyl group; a is 1, 2 or 3.

7. The method for producing a curable composition according to claim 5, wherein the (E) polyoxyalkylene polymer having a silyl group has a number average molecular weight of 3,000 or more and 50,000 or less.

8. A method for producing a cured product, comprising a step of curing the curable composition obtained by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • One-pack type curable composition and cured product

    WO2023048155A1